A novel live-attenuated vaccine candidate for mayaro Fever. - William J Weise; Meghan E Hermance; Naomi Forrester; A Paige Adams; Rose Langsjoen; Rodion Gorchakov; Eryu Wang; Maria D H Alcorn; Konstantin Tsetsarkin; Scott C Weaver (Public Library of Science (PLoS), 2014)
Mayaro virus (MAYV) is an emerging, mosquito-borne alphavirus that causes a dengue-like illness in many regions of South America, and which has the potential to urbanize. Because no specific treatment or vaccine is available for MAYV infection, we capitalized on an IRES-based approach to develop a live-attenuated MAYV vaccine candidate. Testing in infant, immunocompetent as well as interferon receptor-deficient mice demonstrated a high degree of attenuation, strong induction of neutralizing antibodies, and efficacy against lethal challenge. This vaccine strain was also unable to infect mosquito cells, a major safety feature for a live vaccine derived from a mosquito-borne virus. Further preclinical development of this vaccine candidate is warranted to protect against this important emerging disease.